Numerical study of highly efficient centrifugal cyclones - Madaliev, Murodil (Acta hydrotechnica, 2024)
Centrifugal cyclones have been developed for centuries to treat process streams, but their efficiency in removing fine dust remains below 80%. The widespread use of cyclones in various industries is the result of their simplicity in design and their reliable operation. However, the process occurring inside a cyclone is a complex scientific problem that still remains unsolved within the framework of aerohydromechanics, as evidenced by the variety of cyclone designs. The current level of cyclone cleaning's efficiency for process streams does not meet sanitary standards and significantly affects the level of environmental pollution. This paper compares various configurations of centrifugal cyclones, including cyclones without screws, with a screw of a uniform pitch, and with a screw of a variable pitch to regulate the twist of the flow. Numerical simulations were performed using the Comsol Multiphysics 5.6 software package using the SST turbulence model. The obtained numerical data show that the efficiency of a cyclone with a variable screw pitch is significantly higher than that of cyclones without screws and with a screw of a uniform pitch.
Keywords: cikloni; cyclones; hidrologija; hydrology; matematično modeliranje; mathematical modeling; Reynolds-averaged Navier–Stokes equations; Reynoldsovo povprečene Navier-Stokesove enačbe; turbulence models; turbulenčni modeli